Pengembangan bahan ajar IPA terpadu bermuatan literasi saintifik tema peran energi bagi makhluk hidup untuk siswa SMP kelas VII - Nurul Zakiatin Nafsih; Renol Afrizon; Asrizal Asrizal (Universitas Negeri Padang, 2019)
The 21st century education requires human resources who have broad insight, good critical thinking, and good literacy. The Indonesian government created the 2013 curriculum to answer the demands of 21st century education. Science learning in the 2013 curriculum must be implemented in an integrated patter. The real condition at school showed that science learning can’t be implemented properly. One solution to solve this problem is to develop integrated Science learning material with scientific literacy. The purpose of this research was to determine the validity of integrated Science learning material with scientific literacy. The type of research was Research and Development (R & D). The object of the research was the integrated Science learning material with scientific literacy on the theme of the role of energy for living things. The instrument for validating this learning material was a questionnaire sheet. The instrument for evaluating validity was composed of four components, namely the content feasibility, presentation, language, and graphics. The validators to assess the validity of integrated Science learning materials consist of five experts from three physics lectures, one biology lecturer, and one science lecturer. The data analysis technique was descriptive statistics. Based on data analysis, it can be concluded that the average value of validation of integrated Science learning material with scientific literacy on the theme of the role of energy for living things for the four components of assessment of teaching materials was 87.86. Thus, the average value of validation of integrated science learning material can be classified into a very good category.